Comparación de la acumulación de Unidades Térmicas en el Cultivo de Quinua (chenopodiumquinoa), con abonado de fondo, químico, orgánico en el Barrio Guambalo, Cantón Latacunga, Provincia Cotopaxi - Tovar Tobar, Wilson Ramiro (2018)
The research was carried out in Guambaló neighborhood, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, in order to compare the accumulation of thermal units in the quinoa (Chenopodium quinoa), with fertilizer, chemical, organic and testigo (without fertilizer).The methodology used was a randomized complete block design (DBCA) with factorial arrangement 3x2, with 3 replicates, delimiting the plots for each treatment under study, paid with the chemical (10-30-30) and dry manure of guinea pig rabbit, the sowing was done according to the sketch of the test placing 2 -3 seeds By blow, the research data was taken daily from the crop, temperature and relative humidity using a thermometer and digital hygrometer (TA 298), while the height for each variety was taken according to the phenological stage.The results of the research were the determination of the thermal units for each of the varieties of quinoa (Chenopodium quinoa),in the different phenological stages, from the sowing to the panojamiento, resulting from the sowing to emergence 36, 1 GD development)emergency up to two true leaves 129.5 GD from two true leaves to four true leaves, 213.6 GD, from four true leaves to six true leaves, 282.8 GD, from six true leaves to branching 363.1 GD from branching to plowing 491.4 GD.The temperature helps in the development of each phenological stage of the quinoa (Chenopodium quinoa) cultivation, the average temperature of the entire vegetative cycle was 18.16 ° C and the average relative humidity throughout the development of the plant was of 55.05%.It is very noticeable in the vegetal development of the Tunkahuan and Green Promisoria varieties the treatment of without fertilizer those that reached the best averages of height in each one of the phenological phases